0346 Metabolic Aging and Sleep Loss: Metabolite Signatures Link Sleep Deprivation and Aging Across Tissues. (27th May 2020) - Sengupta, A; Tudor, J C; Cusmano, D; Baur, J A; Abel, T; Weljie, A
Abstract: Introduction: Insufficient sleep is a hallmark of modern society, and sleep deprivation (SD) is a risk factor for neurodegenerative and cardiometabolic disorders. The interactions of aging with systemic and local metabolic alterations induced by sleep deprivation are essentially unexplored. In this study, we demonstrate a shared metabolic imprint of SD and aging in plasma, liver, and hippocampus. Methods: Young (2 - 4 months) and aged (22 - 24 months) mice were sleep deprived (N = 10/group) for 5 hours followed by collection of blood plasma, liver and hippocampus. The samples were extracted and subjected to UPLC-MS/MS based targeted metabolomics analysis. Results: Young animals displayed greater sensitivity to SD induced metabolic changes with >40% more metabolites perturbed in each sample type measured compared to aged animals. Enrichment analysis based on known disease-associated metabolites suggests that plasma change in young animals are of pathological relevance, but not in aged animals. A common hepatic signature of sleep-loss across the two age groups consisted of ketosis and urea cycle perturbation. Approximately 20-30% of measured metabolites exhibit similar changes when the sleep deprivation induced signature is compared with the aging metabolic imprint in a tissue-dependent manner. Central energetics, urea cycle and aromatic amino acid metabolism highlight the common pathways altered by sleep and aging in the periphery. In the hippocampus, choline and acetylcholine pools were depleted, potentially providing insight into the changes in metabolism that accompany analogous defects in memory consolidation. Conclusion: These results support the notion that SD makes the 'young seem old'. The results further connect neurobehavioral observations tying together aging and sleep loss, by implicating molecular mechanisms at the level of metabolism. Support: This work was supported by NIH grant R21AG052905 (AMW, AS), P50AG017628 (TA; A.I. Pack, PI) and R01AG062398 (TA, JT). TA was supported by the Brush Family Chair in Biology at Penn and is currently supported by the Roy J. Carver Chair of Neuroscience at Iowa.